Total Quality Manajemen (TQM) Dalam Pengelolaan Sarana Prasarana Pendidikan: Upaya Meningkatkan Akreditasi Sekolah. - Shofiyatul Hasanah; Moh Rofiki (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2026)
This research aims to explore the application of Total Quality Management in the management of infrastructure facilities in order to improve and maintain school accreditation. The focus of the research is the implementation of TQM principles such as (Focus on Customer), (Total Involvement), (Continuous Improvement), to meet the National Education Standards (SNP). With a qualitative approach of the type of case study, this research involves infrastructure managers, teachers, and students to study and get applied results, so that it can affect the quality of school services. The findings show that the principle (Focus on Customer) is a priority for schools in providing facilities according to the needs of service users. Forming a work program through the involvement of all parties (Total Involvement). So that the program becomes a structured work cycle and can become a continuous improvement strategy. The results of this study contribute to developing the application of TQM principles in the management of infrastructure facilities and provide practical management methods in maintaining accreditation in a sustainable manner. And the researcher was able to present updates that lie in TQM specifically applied as an infrastructure management system that acts as a superior accreditation assessment instrument.